Diseño de prototipo hospitalario (2018)
This investigation was based on a proposal of an integral model about a hospitaller design, because there has been found many irregularities the current designs of many hospitals which has a lot of non planed expansions as a principal issue, causing many displacing problems between the different areas of the hospital and this also causes a disorder between septic and aceptic circulations. Another issue that is caused from this, is that there are many spaces that doesn't have natural ventilation and ilumination. In order to improve these problems, it has been developed the proposal of new hospitaller prototype designs, in which every service counts with a standarized space that allows them to have a better atention, more confort, ventilation and vegetation. Thanks to the modules, there are many proyects of any level that can be developed, or it also could me aplied on a planified design of a posible expansion of the building. This design was aplied based on many experiences that were collected by many field investigations and also by bibliografical information, national and international references.